Thermal regime of Negotinska Krajina - Živković Ljiljana; Živković Nenad; Janić-Siridžanski Marina (Glasnik Srpskog Geografskog Društva, 2005)
Negotin Krajina geographically belongs to Mezian tablet that means it is widely open to the influences from the East but main air influences come from the West and North-West causes specific thermal characteristics. Meteorological station "Negotin" is the only one respectable station in the Krajina then we analyze results from various periods since 1901. It is important to emphasize that station "Negotin" doesn't have work continuity since the beginning of the century, thus for analyzing certain climate elements we have had to use method of analogy with station "Zaječar". A part of that, observations were not done by the same methodology so there is lack of some important indicators for this first period. To determine air thermo-regime of Negotin Krajina during 20 century, standard periods (1901-1930., 1931-1960. and 1961-1990) for analyzing climate elements suggested by WMO, were compared. Also, periods from 1925. to 1940. and from 1990. to 2000. were added to this analysis (according to data we had).